Edge even graceful labelling of new families of graphs. Issue 1 (11th December 2019) - Daoud, S. N.; Elsawy, Ahmed N.
ABSTRACT: Elsonbaty and Daoud introduced a new type of labelling of a graph G with p vertices and q edges called an edge even graceful labelling. A graph G is called edge even graceful if there is a bijection f : E ( G ) → { 2, 4, …, 2 q } such that, when each vertex is assigned the sum of all edges incident to it mod 2 k, where k = max ( p, q ), the resulting vertex labels are distinct. In this paper we proved that double fan graphs, quadrilateral friendship graphs, and butterfly graphs are edge even graceful graphs.